Optimization of fermentation parameters for the bioconversion of corn to ethanol using response surface methodology - Walia, Navpreet Kaur (My University, 2013)
The present study was conducted to optimize the ethanol production potential of maize (Zea mays). In order to achieve maximum ethanol production two experiments were conducted by optimizing three fermentation variables i.e. pH, temperature and substrate concentration which were optimized at different conditions using response surface methodology by design- expert software (version 8. 0.7.1 Stat-Ease Inc; USA). Parameters were optimized by two ways: the first experiment is conducted manually by changing one variable at a time and keeping the other two invariable without RSM and second experiment was conducted by central composite design observing the effect of combination of two variables and keeping the one constant on ethanol production. During first experiment, maximum ethanol i.e 78.4 g/L was observed at conditions: pH 5.5, temperature 35⁰C and substrate concentration of 160g. During the second experiment, the maximum ethanol production was 74.6 g/L at conditions: pH 5.8, temperature 31⁰C and substrate concentration 160 g. The RSM is a better method for optimization of parameters as it is less labour intensive. It reduces the number of fermentation batches. The adequacy of all the models was satisfactory as coefficients of determination were found to be (0.9923) (0.9735) (0.9662).
Master of Science-Biotechnology, Dissertation
Keywords: Fermentation, Corn; Ethanol; Response surface methodology